Increased Free Radical Generation during the Interaction of a Quinone-Quinoline Chelator with Metal Ions and the Enhancing Effect of Light - Olga Yu. Selyutina; Simon V. Babenko; Irina A. Slepneva; Nikolay E. Polyakov; George J. Kontoghiorghes (MDPI AG, 2023)
Schiff bases and similar molecules forming metal complexes may cause redox effects, which may also be influenced by light. Anthraquinones such as doxorubicin and idarubicin are widely used antitumor agents, which can generate reactive oxygen species (ROS), stimulated by both the presence of iron and copper ions and also by light. The generated ROS can cause DNA scission, cell membrane oxidation, and many other toxic effects. The redox activity of the quinone-quinoline chelator 2-phenyl-4-(butylamino)naphtho [2,3-h]quinoline-7,12-dione (Q1) was investigated in the presence of iron, copper, and zinc. The influence of light in these interactions was also examined. The chemically induced dynamic nuclear polarization (CIDNP), nuclear magnetic resonance (NMR), and electron paramagnetic resonance (EPR) methods were used to elucidate the molecular changes and ROS generation effects of the Q1 metal interactions. A model electron transfer reaction system between 1,4-dihydropyridine and Q1 was utilized to demonstrate that the chelate complexes of Q1 with both Fe(III) and Cu(II) ions were more redox active than Q1 itself. Similarly, CIDNP and NMR data showed that the concentration dependence of the free radicals yield is much higher in the presence of Fe(III) and Cu(II) ions, in comparison to Zn(II), and also that it increased in the presence of light. These findings underline the role of transition metal ions and Q1 in cyclic redox chain reactions and increase the prospect of the development of copper- and iron-based chelating agents, including Q1 and its derivatives, for anticancer therapy. Furthermore, these findings also signify the effect of light on enhancing ROS formation by Q1 and the prospect of utilizing such information for designing target specific anticancer drugs for photodynamic therapy.